Improving Sustainable Competitive Advantage through Knowledge of Sharia Banking in a Spiritual Well-Being - Nurcahyo, Satria Avianda; Nurani, Bulan Karima; Thoha, Anis Malik; Jayanti, Fitri Dwi (Ekonomi Syariah IAIN Kudus, 2024)
This research aims to analyze the influence of Knowledge of Sharia Banking, Spiritual Well-Being, and Sharia Compliance on Sustainable Competitive Advantage among employees of PT Bank Syariah Indonesia Tbk. The research respondents were employees of PT Bank Syariah Indonesia Tbk in Semarang Residency and Salatiga City, which had a total of 250 people, consisting of 145 male employees and 105 female employees. The sampling technique employed was a census involving direct sampling of the entire population, resulting in 250 responses. The results of empirical testing in this research show that the overall hypothesis is accepted, and Spiritual Well-Being is proven to mediate each relationship between Knowledge of Sharia Banking with Sharia Compliance and Sustainable Competitive Advantage. Even though it has been proven to mediate between the two, the most significant mediating influence of Spiritual Well-Being is between Knowledge of Sharia Banking and Sustainable Competitive Advantage.